2012
DOI: 10.1038/ejhg.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

Gross deletions in TCOF1 are a cause of Treacher–Collins–Franceschetti syndrome

Abstract: Treacher-Collins-Franceschetti syndrome (TCS) is an autosomal dominant craniofacial disorder characterised by midface hypoplasia, micrognathia, downslanting palpebral fissures, eyelid colobomata, and ear deformities that often lead to conductive deafness. A total of 182 patients with signs consistent with a diagnosis of TCS were screened by DNA sequence and dosage analysis of the TCOF1 gene. In all, 92 cases were found to have a pathogenic mutation by sequencing and 5 to have a partial gene deletion. A further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 35 publications
1
45
0
1
Order By: Relevance
“…As described in the literature, the majority of TCOF1 mutations were frameshift mutations, 8 yielding to haploinsufficiency of the Treacle protein. [20][21][22] Bowman et al 8 also described five large deletions in TCOF1 in patients with typical TCS, although the full extent of each deletion was not known because they involved either the first or last exon.…”
Section: Molecular Datamentioning
confidence: 85%
See 3 more Smart Citations
“…As described in the literature, the majority of TCOF1 mutations were frameshift mutations, 8 yielding to haploinsufficiency of the Treacle protein. [20][21][22] Bowman et al 8 also described five large deletions in TCOF1 in patients with typical TCS, although the full extent of each deletion was not known because they involved either the first or last exon.…”
Section: Molecular Datamentioning
confidence: 85%
“…In the literature, the percentage of patients with mutations in TCOF1 ranged from 53% (97/182) 8 to 93% (26/28). 2,8,18 In the study by Bowman et al, 8 the proportion increased from 53 to 71% if patients with a high clinical suspicion of TCS are considered, and in the study by Teber et al 2 it increased from 61 to 78%.…”
Section: Molecular Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Further use of this model should demonstrate the exact role of TCOF1 in the formation of TCS. The other studies of TCS1 etiology that have been carried out on the human genome have revealed that not only single mutations are responsible for the TCS; it can also occur on the basis of the total rearrangement of the TCOF1 gene [60].…”
Section: Pierre Robin Sequencementioning
confidence: 99%